2008
DOI: 10.1590/s0104-11692008000700018
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem, perceived self-efficacy, consumption of tobacco and alcohol in secondary students from urban and rural areas of Monterrey, Nuevo León, México

Abstract: NN. Self-esteem, perceived self-efficacy, consumption of tobacco and alcohol in secondary students from urban and rural areas of Monterrey, Nuevo León, México. Rev Latino-am Enfermagem 2008 maio-junho; 16(especial):614-20 This study aimed to know the differences, if any, in the consumption of tobacco and alcohol among adolescents from urban and rural areas, and if self-esteem and self-efficacy are related to the consumption in these two groups of adolescents from secondary schools in urban and rural areas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…For example, individuals from small rural areas seem to incorporate themselves into adulthood early in life, thus reporting increased participation in non-healthy behaviors. The fact that risk behaviors tend to increase again in larger cities could be related to a higher exposure to incentives to participate in these behaviors, such as higher prevalence in the community and a higher presence of marketing in larger areas [42]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, individuals from small rural areas seem to incorporate themselves into adulthood early in life, thus reporting increased participation in non-healthy behaviors. The fact that risk behaviors tend to increase again in larger cities could be related to a higher exposure to incentives to participate in these behaviors, such as higher prevalence in the community and a higher presence of marketing in larger areas [42]. …”
Section: Discussionmentioning
confidence: 99%
“…With a trend of increasing prevalence of smoking among adolescents, interventions are being targeted to this group. In addition, because risk behaviors usually reinforce each other, alcohol and drug consumption are also public health concerns regarding adolescents in Mexico, with a vast literature addressing these behaviors and their correlates [42,45-47]. …”
Section: Discussionmentioning
confidence: 99%
“…Perceived self-efficacy is therefore essential in coping with events that the person considers threatening so that the higher the self-efficacy, the lower the stress level and the greater the ability to adapt [ 29 , 30 ]. Having a high level of self-efficacy improves both the confidence that people have in themselves, as well as in their abilities [ 31 , 32 ], which also contributes to an increase in emotional well-being, quality of life and coping with stressful situations [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Finally, factors such as alcohol and tobacco use are weak predictors of self-efficacy. 21,22 Several studies using functional MRI and PET scans have shown that brain development begins from behind and towards the front, that is, the hypothalamic limbic system (which controls our emotions) matures first and the prefrontal cortex (which controls the hypothalamic limbic system and helps to make rational decisions with an ability to see the future consequences of one's actions) matures last-at around 25 years. Hence, it is expected that there may be agebased differences in brain development among adolescents (17-19 yrs.)…”
Section: Introductionmentioning
confidence: 99%